2019
DOI: 10.1101/2019.12.26.19015560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying groups of people with similar sociobehavioural characteristics in Malawi to inform HIV interventions: a Latent Class Analysis

Abstract: Background: Within many sub-Saharan African countries including Malawi, HIV prevalence varies widely between regions. This variability may be related to the distribution of population groups with specific sociobehavioural characteristics that influence the transmission of HIV and the uptake of prevention. In this study, we intended to identify groups of people in Malawi with similar risk profiles. Methods: We used data from the Demographic and Health Survey in Malawi from 2016, and stratified the analysis by… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Moreover, it is possible that sexual partners may contribute to a commitment to getting an HIV testing done. Analyses of survey data from Malawi and Uganda revealed higher HIV prevalence among people who were not in marital unions [8,22,25,26]. This is consistent with our findings and suggests need to encourage more testing and safer sexual practices among sexually active individuals who are not in committed relationships.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, it is possible that sexual partners may contribute to a commitment to getting an HIV testing done. Analyses of survey data from Malawi and Uganda revealed higher HIV prevalence among people who were not in marital unions [8,22,25,26]. This is consistent with our findings and suggests need to encourage more testing and safer sexual practices among sexually active individuals who are not in committed relationships.…”
Section: Discussionsupporting
confidence: 88%
“…We designed the review to be broad and inclusive to capture all possibly relevant factors and expected it to identify known factors, neglected factors, and some factors that may never have been identified or analyzed in quantitative studies. We chose Malawi because 1) Malawi has relatively high HIV prevalence that varies substantially between regions [16]; 2) the country is socio-culturally diverse because it is home to many ethnic groups (e.g., Chewa, Nyanja, Tumbuka, Yao, Lomwe, Sena, Tonga, Ngoni, Ngonde, Asians, and Europeans); 3) a preliminary search revealed that Malawi was the focus of many scientific studies on HIV, including some by our group [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…We designed the review to be broad and inclusive to capture all possible relevant factors and expected it to identify known factors, neglected factors, and some factors that may never have been identified or analyzed in quantitative studies. We chose Malawi for several reasons: (1) Malawi has a relatively high HIV prevalence that varies substantially between regions [16], (2) the country is socioculturally diverse because it is home to many ethnic groups (eg, Chewa, Nyanja, Tumbuka, Yao, Lomwe, Sena, Tonga, Ngoni, Ngonde, Asians, and Europeans), and (3) a preliminary search revealed that Malawi was the focus of many scientific studies on HIV, including some by our group [17][18][19].…”
Section: Introductionmentioning
confidence: 99%